Les multiples racines de la certitude de la foi: Durand de Saint-Pourçain et Pierre de Palud, lecteurs de Thomas d'Aquin - Piché, David (Recherches de théologie et philosophie médiévales, 2024)
Medieval theologians contributed greatly to the history of epistemology by reflecting critically on its key concepts. This is particularly the case for the notion of certainty, which they analyzed in the context of their doctrines of religious faith. Based mainly on texts by Thomas Aquinas, Durand of Saint-Pourçain, and Peter of Palud, this article aims to show that two competing conceptions of certainty were discussed in the debates of the time, which I call respectively ‘objectivist’ and ‘subjectivist’. In doing so, in addition to original analyses of texts already known by Aquinas and the Modern Doctor, I propose the very first study of Peter of Palud’s ideas on the certainty of faith.